Portraying Learner’s Autonomy in Extensive Reading Classroom - Fatimah, Asri Siti (OKARA: Jurnal Bahasa dan Sastra, 2019)
Extensive reading, the activities to read a large amount of text and enjoyable input, becomes important to study since it has so many benefits for increasing the studentsâ€™ language competence. It has been noticed that this kind of activity really engages the students because it allows them to receive a large amount of comprehension in a leisure way. In this activity, they may also choose any reading sources and materials that are extremely enjoyable, and suitable with their level and interest promoting their learning autonomy which are responsible for their own learning. Thus this study has the purpose to portray the characteristics of their autonomous learning while joining extensive reading classroom. In this study, blog as instructional technology is used as a learning platform for supporting them conduct extensive reading activities.Â To collect the data, interview was given to six students who become participants of the study. It aimed to deeply investigate their autonomous learning while doing extensive reading. The findings show that there are several characteristics of autonomous learning in this class. They are setting the goal of their learning, adjusting learning strategies to improve learning, knowing how to use resources autonomously, managing the time properly, and having motivation to learn independently.